Nanay cocha - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Vista aérea del Río Amazonas y su afluente el Río Nanay
ENGLISH: Aerial view of the Amazon River and its tributary, the Nanay River.

SPANISH: Vista aérea del Río Amazonas y su afluente el Río Nanay
ENGLISH: Aerial view of the Amazon River and its tributary, the Nanay River.
Nanay cocha
Keywords: Iquitos (Perú)|~|Architecture|~|Rural|~|Amazon|~|Nature|~|Jungles|~|Paisajes|~|Iquitos (Perú)|~|Iquitos (Perú)|~|arquitectura|~|rural|~|naturaleza|~|junglas